## How to Simplify Radical Expressions Involving Fractions

### Simplifying Radical Expressions Involving Fractions

We have discussed Simplifying Radical Expressions here. Now we are going to learn how to simplify Radical Expressions Involving Fractions.

### Step by Step How to Simplify Radical Expressions Involving Fraction

To make fractional radical expressions simpler:

• If the denominator contains a radical, multiply that radical by the numerator and denominator.
• Multiply both the numerator and the denominator by the conjugate of the denominator if the denominator contains both a radical and another integer.

Let's see some solved examples that help to understand better.

### Example1

Simplify $$\frac{2}{\sqrt{3}}$$

Solution:

Multiply $$\sqrt{3}$$ by the numerator and denominator: $$\frac{2}{\sqrt{3}} \times \frac{\sqrt{3}}{\sqrt{3}} \ = \ \frac{2\sqrt{3}}{3}$$

### Example2

Simplify $$\frac{5}{1 \ - \ \sqrt{11}}$$

Solution:

Multiply the numerator and denominator by the conjugate of the denominator:

$$\frac{5}{1 \ - \ \sqrt{11}} \times \frac{1 \ + \ \sqrt{11}}{1 \ + \ \sqrt{11}} \ = \ \frac{5 \ + \ 5\sqrt{11}}{1^2 \ + \ (\sqrt{11})^2} \ = \ \frac{5 \ + \ 5\sqrt{11}}{12}$$

### Exercises for Simplifying Radical Expressions Involving Fractions

1) Simplify: $$\frac{\sqrt{125 \ n^5}}{\sqrt{5 \ n}}$$

2) Simplify: $$\frac{\sqrt{108 \ x^{11}}}{\sqrt{6 \ x^2}}$$

3) Simplify: $$\frac{\sqrt{66 \ n^6}}{\sqrt{22 \ n^2}}$$

4) Simplify: $$\frac{5}{\sqrt{3}}$$

5) Simplify: $$\frac{6 \ \sqrt{2x}}{\sqrt{x}}$$

6) Simplify: $$\frac{3 \ \sqrt{72 \ x^3}}{\sqrt{12x}}$$

7) Simplify: $$\frac{\sqrt{70 \ x^7}}{\sqrt{5x^2}}$$

8) Simplify: $$\frac{\sqrt{36 \ x^2}}{\sqrt{12x^5}}$$

9) Simplify: $$\frac{\sqrt{69 \ m^7}}{\sqrt{23 \ m^{12}}}$$

10) Simplify: $$\frac{7}{1 \ + \ \sqrt{z}}$$

1) Simplify: $$\frac{\sqrt{125 \ n^5}}{\sqrt{5 \ n}}$$

$$\color{red}{\frac{\sqrt{125 \ n^5}}{\sqrt{5 \ n}} \ = \ \frac{\sqrt{5^2 \times 5 \ n^{2 \times 2} \times n}}{\sqrt{5 \ n}} \ = \ \sqrt{5^2 \ n^{2 \times 2}} \ = \ 5 \ n^2}$$

2) Simplify: $$\frac{\sqrt{108 \ x^{11}}}{\sqrt{6 \ x^2}}$$

$$\color{red}{\frac{\sqrt{108 \ x^{11}}}{\sqrt{6 \ x^2}} \ = \ \frac{\sqrt{3^3 \times 2^2 \ x^{2 \times 4} \times x^2 \times x}}{\sqrt{2 \times 3 \ x^2}} \ = \ \sqrt{3^2 \ x^{2 \times 4} \times x} \ = \ 3 \ x^4 \sqrt{x}}$$

3) Simplify: $$\frac{\sqrt{66 \ n^6}}{\sqrt{22 \ n^2}}$$

$$\color{red}{\frac{\sqrt{66 \ n^6}}{\sqrt{22 \ n^2}} \ = \ \frac{\sqrt{6 \times 11 \ n^{2 \times 3}}}{\sqrt{2 \times 11 \ n^{2 \times 1}}} \ = \ \sqrt{6 \ n^{2 \times 2}} \ = \ n \ \sqrt{6}}$$

4) Simplify: $$\frac{5}{\sqrt{3}}$$

$$\color{red}{\frac{5}{\sqrt{3}} \ = \ \frac{5}{\sqrt{3}} \times \frac{\sqrt{3}}{\sqrt{3}} \ = \ \frac{5 \ \sqrt{3}}{3}}$$

5) Simplify: $$\frac{6 \ \sqrt{2x}}{\sqrt{x}}$$

$$\color{red}{\frac{6 \ \sqrt{2x}}{\sqrt{x}} \ = \ \frac{6 \ \sqrt{2x}}{\sqrt{x}} \times \frac{\sqrt{x}}{\sqrt{x}} \ = \ \frac{6 \ \sqrt{2 \ x^2}}{x} \ = \ \frac{6 \ x \ \sqrt{2}}{x} \ = \ 6 \ \sqrt{2}}$$

6) Simplify: $$\frac{3 \ \sqrt{72 \ x^3}}{\sqrt{12x}}$$

$$\color{red}{\frac{3 \ \sqrt{72 \ x^3}}{\sqrt{12x}} \ = \ 3 \ \sqrt{\frac{72 \ x^3}{12x}} \ = \ 3 \ \sqrt{6 \ x^2} \ = \ 3 \ x \ \sqrt{6}}$$

7) Simplify: $$\frac{\sqrt{70 \ x^7}}{\sqrt{5x^2}}$$

$$\color{red}{\frac{\sqrt{70 \ x^7}}{\sqrt{5x^2}} \ = \ \sqrt{\frac{70 \ x^7}{5x^2}} \ = \ \sqrt{14 \ x^5} \ = \ x^2 \ \sqrt{14x}}$$

8) Simplify: $$\frac{\sqrt{36 \ x^2}}{\sqrt{12x^5}}$$

$$\color{red}{\frac{\sqrt{36 \ x^2}}{\sqrt{12x^5}} \ = \ \sqrt{\frac{36 \ x^2}{12x^5}} \ = \ \sqrt{\frac{3}{x^3}} \ = \ \frac{\sqrt{3}}{x \ \sqrt{x}} \ = \ \frac{\sqrt{3}}{x \ \sqrt{x}} \times \frac{\sqrt{x}}{\sqrt{x}} \ = \ \frac{\sqrt{3x}}{x \ \sqrt{x^2}} \ = \ \frac{\sqrt{3x}}{x^2}}$$

9) Simplify: $$\frac{\sqrt{69 \ m^7}}{\sqrt{23 \ m^{12}}}$$

$$\color{red}{\frac{\sqrt{69 \ m^7}}{\sqrt{23 \ m^{12}}} \ = \ \sqrt{\frac{69 \ m^7}{23 \ m^{12}}} \ = \ \sqrt{\frac{3}{m^5}} \ = \ \frac{\sqrt{3}}{m^2 \ \sqrt{m}} \ = \ \frac{\sqrt{3}}{m^2 \ \sqrt{m}} \times \frac{\sqrt{m}}{\sqrt{m}} \ = \ \frac{\sqrt{3m}}{m^2 \ \sqrt{m^2}} \ = \ \frac{\sqrt{3m}}{m^3}}$$

10) Simplify: $$\frac{7}{1 \ + \ \sqrt{z}}$$

$$\color{red}{\frac{7}{1 \ + \ \sqrt{z}} \ = \ \frac{7}{1 \ + \ \sqrt{z}} \times \frac{1 \ - \ \sqrt{z}}{1 \ - \ \sqrt{z}} \ = \ \frac{7 \ - \ 7 \ \sqrt{z}}{1 \ - \ z}}$$

## Simplifying Radical Expressions Involving Fractions Practice Quiz

### STAAR Grade 8 Math Study Guide

$19.99$14.99

### ACT Mathematics Formulas

$6.99$5.99

### PSAT Math Full Study Guide

$25.99$13.99

### PSAT Math for Beginners

$24.99$14.99